Media Pendidikan Dalam Perspektif Pendidikan Islam - Unang Wahidin; Ahmad Syaefuddin (Sekolah Tinggi Agama Islam Al Hidayah, 2018)
The development of science and technology increasingly encourage renewal efforts in the utilization of technology results in teaching and learning process. One of the technology that can be used in teaching and learning process is education media. Educational media used must be adapted to the development and demands of the times. Support the right educational media used in teaching and learning process will facilitate the achievement of learning objectives can be. Therefore, the education media will affect the absence of a complete and appropriate learning information target, and affect the outcome of the learning process. At the beginning of the spread of Islam has been known teaching and learning activities, when the media has been there and education has been applied by the Prophet Muhammad SAW in teaching science and Islamic law to the friends. Some educational media clusters expressed in the Qur'an and al-Hadith, among others: Audio education media contained in al-Qur'an letter al-'Alaq (96) verse 1; Al-Isra '(17) verse 14; Al-Ankabut (29) verse 45; Al-Muzammil (73) verse 20. In addition, in the hadith there are several terms used to indicate the use of visual media in learning, such as drawings, gravel and fingers.Â Keyword: Media, Education, Islam, Al-Qurâ€™an